Low frequency noise and radiation response in the partially depleted SOI MOSFETs with ion implanted buried oxide *Project supported by the National Natural Science Foundation of China (Grant Nos. 61204112 and 61204116). (August 2015) - Liu, Yuan; Chen, Hai-Bo; Liu, Yu-Rong; Wang, Xin; En, Yun-Fei; Li, Bin; Lu, Yu-Dong
Abstract Low frequency noise behaviors of partially depleted silicon-on-insulator (PDSOI) n-channel metal-oxide semiconductors (MOS) transistors with and without ion implantation into the buried oxide are investigated in this paper. Owing to ion implantation-induced electron traps in the buried oxide and back interface states, back gate threshold voltage increases from 44.48 V to 51.47 V and sub-threshold swing increases from 2.47 V/dec to 3.37 V/dec, while electron field effect mobility decreases from 475.44 cm2/V·s to 363.65 cm2/V·s. In addition, the magnitude of normalized low frequency noise also greatly increases, which indicates that the intrinsic electronic performances are degenerated after ion implantation processing. According to carrier number fluctuation theory, the extracted flat-band voltage noise power spectral densities in the PDSOI devices with and without ion implantation are equal to 7×10−10 V2·Hz−1 and 2.7×10−8 V2·Hz−1, respectively, while the extracted average trap density in the buried oxide increases from 1.42×1017 cm−3·eV−1 to 6.16×1018 cm−3·eV−1. Based on carrier mobility fluctuation theory, the extracted average Hooge's parameter in these devices increases from 3.92×10−5 to 1.34×10−2 after ion implantation processing. Finally, radiation responses in the PDSOI devices are investigated. Owing to radiation-induced positive buried oxide trapped charges, back gate threshold voltage decreases with the increase of the total dose. After radiation reaches up to a total dose of 1 M·rad(si), the shifts of back gate threshold voltage in the SOI devices with and without ion implantation are −10.82 V and −31.84 V, respectively. The low frequency noise behaviors in these devices before and after radiation are also compared and discussed.